Student science literacy ability in Basidiomycota material content aspect - Salwa Rezeqi; Novayanti Gultom (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
This research was conducted in relation to the demands of the 21st century, namely the ability to solve every problem encountered, with the measurement of scientific literacy skills in content aspects can overcome problems in everyday life for students. The research aims to determine scientific literacy skills in aspects of student content on the Basidiomycota topic. This research was conducted at the Biology Department, FMIPA, Medan State University. The population of this study were all 122 students of the Biology Study Program class of 2021 at Medan State University. The sample of this research is 31 people using purposive sampling technique. The research design is quantitative descriptive. The results of research on scientific literacy abilities on aspects of student content on the Basidiomycota topic are in the conceptual science literacy category with an average percentage of 78.02%. The results of this study indicate that the conceptual scientific literacy category of students is still at the stage of understanding the Basidiomycota topic conceptually or in general and does not yet have a specific understanding. These results can be improved by looking for accurate references to journals and books in order to better understand the Basidiomycota topic so that their scientific literacy skills reach the category of multidimensional scientific literacy.Abstrak Penelitian ini dilakukan berkaitan dengan tuntutan abad 21 yaitu kemampuan untuk menyelesaikan setiap permasalahan yang dihadapi, dengan adanya pengukuran kemampuan literasi sains pada aspek konten dapat mengatasi permasalahan dalam kehidupan sehari-hari bagi mahasiswa. Penelitian bertujuan untuk mengetahui kemampuan literasi sains pada aspek konten mahasiswa pada topik Basidiomycota. Penelitian ini dilaksanakan di Jurusan Biologi FMIPA Universitas Negeri Medan. Populasi penelitian ini adalah seluruh mahasiswa Program Studi Biologi angkatan 2021 Universitas Negeri Medan yang berjumlah 122 orang. Sampel penelitian ini berjumlah 31 orang dengan menggunakan teknik purposive sampling. Desain penelitian ini adalah deskriptif kuantitatif. Hasil penelitian kemampuan literasi sains pada aspek konten mahasiswa topik Basidiomycota dalam kategori literasi sains konseptual dengan persentase rata-rata 78,02%. Hasil penelitian tersebut menunjukkan kategori literasi sains konseptual mahasiswa masih pada tahap mengerti topik Basidiomycota secara konsep atau secara umum dan belum memiliki pemahaman secara spesifik. Hasil tersebut dapat ditingkatkan dengan mencari referensi jurnal dan buku yang akurat agar semakin memahami topik Basidiomycota sehingga kemampuan literasi sainsnya mencapai kategori literasi sains multidimensi.